Prevalence of breast cancer in patients undergoing microdochetomy for a pathological nipple discharge - Lesetedi, Chiapo (My University, 2016)
ntroduction Although a pathological nipple discharge can be associated with breast cancer, most of the causes are benign. The current gold standard for diagnosis is microdochectomy and this means that many women will undergo this invasive procedure for benign causes. Demographic data of patients, clinical characteristics, and preoperative radiological investigations which can select patients at risk of cancer may help to reduce the number of patients operated for benign causes but there is little data to confirm this, especially from sub-Saharan Africa. Aim This study aimed to determine the prevalence of cancer in patients who had microdochectomy for pathological nipple discharge in a population in South Africa and evaluate patients’ demographics and clinical characteristics as indicators of underlying cancer. Patients and methods Clinical, radiological and histological data from 153 patients who underwent a microdochectomy for a pathological nipple discharge at two South African breast clinics was collected. Results Invasive or in-situ cancer was found in 12 patients (7.84%) and in all patients, cancer was associated with a bloody nipple discharge. Bloody discharge had a sensitivity of 100% in indicating cancer, specificity of 55.32%, positive predictive value of 16%, and negative predictive value of 100%. Patients with breast cancer were also more likely to be above 50 years (p=0.04). Preoperative mammogram and ultrasound were poor in detecting cancer (0/12). Conclusion In our population, patients with an isolated bloody nipple discharge (no mass) should have microdochectomy done, while many other patients can be managed expectantly with surgery only offered in individualised cases. Thorough clinical examination to determine the true colour and nature of the discharge is vital in the initial assessment of these patients. Preoperative radiology is not helpful in determining the presence of cancer (in an isolated pathological nipple discharge) and microdochectomy still remains the gold standard in diagnosing cancer in these patients.
Keywords: Microdochectomy; Breast Neoplasms; Nipple Discharge